Optimalisasi Pengembangan Ekonomi Kreatif Berbasis Sumber Daya Laut Perikanan Di Desa Lojejer, Kecamatan Wuluhan Melalui Edukasi Dan Pendampingan Pengolahan Ikan Hasil Tangkapan Nelayan - Anggraini, Cristian Rizqi; Bakti, Budi Satria; Sandy, Syah Riza Octavy (Universitas Muhammadiyah Jember, 2023)
Lojejer Village, Wuluhan District, is a village where the average person works as a fisherman in Jember Regency. The results of the observations explain the obstacles experienced by the community including: 1) The unstable selling price of cob fish which is still low, 2) not having insight into the process of managing marine catches so that the selling price is high, 3) The lack of community skills to innovate so as to produce products with high selling prices. The next stage is the preparation of monitoring and evaluation instruments, namely community insights, including the process of managing cob fish as shredded products, preparing attractive logo designs and product packaging so that they can be marketed, and managing permits after creating new products, promoting through social media and others. The result of this training is that training and education on the process of making Shredded Cob is carried out as a solution to increase the income of fishermen and home industry processing groups in Lojejer Village will manage the catch and then can be marketed at a higher price